The Effect Of Hand Wash Training On Hand Higyene Behavior In Elementary School Students at SDAI Baznas South Sulawesi - Akbar Asfar; Sudarman Sudarman; Haeril Amir (Universitas STRADA Indonesia, 2020)
The research method is a quasi experiment with the design used is the pretest-posttest control group design. The population taken in this study are school children in SDAI BAZNAS South Sulawesi. The population of the study were 75 students with a sampling technique that is Total Sampling. Data collection techniques with questionnaires and direct observation before and after training 6 steps hand washing. The data collected was analyzed by the Wilcoxon test. The results showed there was an influence of 6 steps hand washing training with Hand Higyene Behavior (Knowledge, Attitudes and Actions) with p = 0,000 <0.005. Thus it was concluded that health education about hand washing had a major influence on behavior change and it was suggested that the need to continue to increase the knowledge and awareness of the community especially students in terms of washing hands, especially in the era of the Covid 19 pandemic